2007
DOI: 10.1159/000099158
|View full text |Cite
|
Sign up to set email alerts
|

Selective Decline in Information Processing in Subgroups of Multiple Sclerosis: An 8-Year Longitudinal Study

Abstract: Multiple sclerosis (MS) is an inflammatory and degenerative disease of the central nervous system (CNS) that causes white matter and cortical lesions over many years. The CNS is selectively affected by the disease with a great variety of symptoms between patients. In this study, we describe the impact on various aspects of cognition over an 8-year follow-up period in 31 consecutive MS patients subgrouped as relapsing remitting (RR) MS, secondary progressive (SP) MS, and primary progressive (PP) MS. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
79
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 83 publications
11
79
0
11
Order By: Relevance
“…A degree of controversy exists on the correlation between cognitive impairment and the degree of physical disability measured with the EDSS scale [5,[27][28][29][30]. We found that SDMT decline was associated with the progression of physical disability.…”
Section: Discussionmentioning
confidence: 78%
“…A degree of controversy exists on the correlation between cognitive impairment and the degree of physical disability measured with the EDSS scale [5,[27][28][29][30]. We found that SDMT decline was associated with the progression of physical disability.…”
Section: Discussionmentioning
confidence: 78%
“…It is important to identify CI as early as possible and to monitor CI frequently. CI may have predictive utility for disease progression (26) and it has been shown that neuropsychological rehabilitation can improve attention, information processing and executive functions in MS patients with low disability levels (27). The PASAT is subject to practice effects(7) and can be affected by educational level, anxiety and motor delay of speech; many patients dislike performing the PASAT, a consideration especially important in the context of clinical trials in which repeated testing might increase the dropout rate (28).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Although many domains of cognition may be affected, one of the most affected in people with MS is the ability to rapidly process information. [6][7][8][9] This ability has been linked to working memory, another cognitive construct that is also frequently affected in MS. [10][11][12] Much of the research on working memory in people with MS has compared the ability to perform rapidly or accurately under a high working memory load. [10][11][12] The prevailing hypothesis is that people with MS have deficits in processing speed and working memory, both of which negatively affect performance as task difficulty increases.…”
mentioning
confidence: 99%